Implementation of 3D Printing Technology in the Food Industry - Sukindar, Nor Aiman; Mohd Samsuddin, Noorazizi; Syed Shaharuddin, Sharifah Imihezri; Kamaruddin, Shafie; Ahmad Azhar, Ahmad Zahirani; Yang, Chuan Chong; Ab Wahab, Muhammad Adil (Academic Research Publishing Group, 2021)
This project involves the implementation of 3D printing technology on designing and fabricating food holders in the food industry. Food holders are designed to hold the food packages in the filling line for food manufacturing industries that apply retort technology. Therefore, this study aims to implement the 3D printing technology in particular FDM to fabricate food holders for the food processing industry. The approach of using this technology is focused on giving more view on the capability of 3D printing technology, aiming at reducing the overall process fabrication cost and fabrication time. Hence, the fabrication cost and time between FDM and conventional machining methods were compared. This study revealed that Organic Gain food industry was able to reduce the cost and fabrication time for the food holder up to approximately 96.3% and 72% respectively. This project gives an insight into the ability of 3D printing technology in delivering the demands of the industry in producing parts as well as the adaptability of the technology to the industry in new product development. The project was carried out successfully and the 3D printed food holder has been tested and functions smoothly